2006
DOI: 10.1210/en.2005-1627
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone Increases β-Catenin Levels through Smad3 in Mouse Osteoblastic Cells

Abstract: PTH, via the PTH/PTH-related protein receptor type 1 that couples to both protein kinase A (PKA) and protein kinase C (PKC) pathways, and the canonical Wnt-beta-catenin signaling pathway play important roles in bone formation. In the present study we have examined the interaction between the PTH and Wnt signaling pathways in mouse osteoblastic MC3T3-E1 cells. PTH dose- and time-dependently increased the concentrations of beta-catenin. The PKA activator, forskolin, and the PKC activator, phorbol 12-myristate-13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
94
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 36 publications
8
94
0
Order By: Relevance
“…The Wnt/␤-catenin signaling pathway plays a pivotal role in osteoblast differentiation and maturation from MSCs (39), and PTH increases the ␤-catenin level in osteoblasts (40). Interestingly, active ␤-catenin increased markedly in NHERF1-null MSC cells (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…The Wnt/␤-catenin signaling pathway plays a pivotal role in osteoblast differentiation and maturation from MSCs (39), and PTH increases the ␤-catenin level in osteoblasts (40). Interestingly, active ␤-catenin increased markedly in NHERF1-null MSC cells (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, the inhibition of Wnt signaling may contribute to the dramatic decrease in the pool of osteoprogenitors in G s α OsxKO mice. In addition to sclerostin and Dkk1, several laboratories have demonstrated other points of interaction between the PTH/PPR/PKA and Wnt signaling pathways (21,47). PTH is able to activate β-catenin targets in osteoblasts even in the absence of Dkk1 suppression (25,26), implicating other actions downstream of the PPR in regulating Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we showed that PTH stimulates osteoblast ␤-catenin levels via Smad3 (10,11). In that study, PTH * This work was supported by a grant from Mitsui Life Social Welfare Foundation (to H. K.), Grants-in-aid 17590961 and 21591179 from the Ministry of Science, Education, and Culture of Japan (to H. K.), the Global COE Program F11 from the Ministry of Education, Culture, Sports, Science, and Technology of Japan, and Canadian Institutes of Health Research Grant MOP-9315 (to G. N. H.).…”
mentioning
confidence: 88%
“…SB431542 and anti-Osterix antibody were from Tocris Cookson Ltd. (Bristol, UK) and Abcam Inc. (Cambridge, MA), respectively. The vectors expressing Myc-tagged Smad3 and a mutant, Smad3⌬C, in which the MH2 domain corresponding to amino acid residues 278 -425 had been removed, were described previously (9,10). All other chemicals used were of analytical grade.…”
mentioning
confidence: 99%